On Welfare Effects of Horizontal Mergers with Product Differentiation - Escrihuela Villar, Marc (2011)
We use a non-spatial (Chamberlinian) product differentiation model to analyze the welfare effects of horizontal mergers with quantity competition. We argue that (i) mergers can be welfare enhancing if the degree of product differentiation increases after the merger; and, (ii) privately profitable mergers can also increase welfare. Consequently, in this paper we demonstrate that the degree of product differentiation is a crucial factor to assess the welfare effects of a merger.